Life Cycles of the Agricultural Consumption Cooperative - AFANASYEVA, Mariya; KARMYSHOVA, Julija (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The modern state of the agricultural economy is characterized by the international crisis, sanctions and solution of the food security issue. In Russia this situation is aggravated by the agricultural territorial degradation, rural depopulation and village infrastructure depreciation. The international and Russian experience shows that one of the key factors of fighting this situation is the establishment of non-commercial organizations in the rural area, namely agricultural consumption cooperatives. Nowadays the Russian cooperative movement is characterized by the low values of the activity effectiveness, that’s why the question arises about searching the ways for the organizational growth and establishment of the consumption cooperatives in the agriculture. The life cycles of organizations, including non-commercial ones, have been taken as a methodological basis of the research. Based on studied models of the life cycles, the hypothesis about four-staged life cycle of the agricultural consumption cooperative has been built. The operation time and development values (earnings, number of shareholders, assortment of services, maintenance sufficiency; information sufficiency) serve as the basic criteria for distinguishing the stages. The empirical research enabled to determine that more than 85% cooperatives in Russia are in the stage of establishment and only 5% assuredly proceeded to the growth stage, in connection with it in the article the model of cooperative transition from the establishment stage to the growth stage and factors of the establishment procedure of the agricultural consumer cooperative were considered.